Searches for excited fermions in ep collisions at HERA - Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; et al. (2002)
Searches in ep collisions for heavy excited fermions have been performed with the ZEUS detector at HERA. Excited states of electrons and quarks have been searched for in e+ p collisions at a centre-of-mass energy of 300 GeV using an integrated luminosity of 47.7 pb-1. Excited electrons have been sought via the decays e± → eγ, e± → eZ and e± → vW. Excited quarks have been sought via the decays q± → qγ and q± → qW. A search for excited neutrinos decaying via v± → vγ, v± → vZ and v± → eW is presented using e-p collisions at 318 GeV centre-of-mass energy, corresponding to an integrated luminosity of 16.7 pb-1. No evidence for any excited fermion is found, and limits on the characteristic couplings are derived for masses ≲250 GeV. © 2002 Elsevier Science B.V. All rights reserved.